2013
DOI: 10.1097/ta.0b013e3182984831
|View full text |Cite
|
Sign up to set email alerts
|

Mortality increases with recurrent episodes of nonaccidental trauma in children

Abstract: Mortality is significantly higher in children who experience rNAT. Therefore, it is critically important to effectively intervene with appropriate resources and follow-up after a child's initial episode of NAT to prevent a future catastrophic episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 16 publications
0
63
0
Order By: Relevance
“…Deans et al [9] describe a mortality rate of 24.5% with recurrent nonaccidental trauma compared with 9.9% mortality in a single event of nonaccidental trauma. Abusive events escalate in severity at an alarming rate, and identification of abusive injuries at the onset may be lifesaving. ]…”
Section: Early Identification Of Child Abusementioning
confidence: 96%
“…Deans et al [9] describe a mortality rate of 24.5% with recurrent nonaccidental trauma compared with 9.9% mortality in a single event of nonaccidental trauma. Abusive events escalate in severity at an alarming rate, and identification of abusive injuries at the onset may be lifesaving. ]…”
Section: Early Identification Of Child Abusementioning
confidence: 96%
“…9 intervention, abuse may recur in nearly 35% to 50% of cases, and death may occur before the subsequent evaluation in nearly 25%. 10,11 The key to accurate diagnosis is a high level of clinical suspicion and a good understanding of the definitions.…”
Section: Emergency Department Epidemiologymentioning
confidence: 99%
“…These physicians concluded that 4 of the 5 deaths reported in this cohort could have been prevented by proper detection and subsequent treatment. This study highlights the large number of children we may be missing in terms of child abuse detection leading to increased injury and mortality for these children [6].…”
Section: Constellation Of Symptoms/differential Diagnosismentioning
confidence: 99%
“…This is particularly true, as catching child abuse in its earliest stages is paramount to preventing mortality. The literature shows that missed injury and multiple-incident child abuse are related to increase in mortality [6,7]. In one study, those children with multiple diagnosed episodes of child abuse had significantly higher mortality than those diagnosed only a single time (24.5 versus 9.9 % mortality, p = 0.002) [6].…”
Section: Introductionmentioning
confidence: 99%